DAMPAK EKSPANSI PERKEBUNAN KELAPA SAWIT TERHADAP SOSIAL EKONOMI MASYARAKAT SEKITAR HUTAN DI DESA PASAK PIANG KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Nurhayati, .; Roslinda, Emi; Rifanjani, Slamet (Universitas Tanjungpura, 2018)
The conversion of forest land functions is the change in the principal function of the forest into non-forest areas such as settlements, agricultural areas and plantations. This happened in Pasak Piang Village, the land turned into an oil palm plantation. This condition will certainly have an impact on the socio-economic community. This research aims to examine the socio-economic changes of the communities surrounding the forest before and after the establishment of an oil palm plantation company.This study uses descriptive analysis of income, production costs, equipment depreciation costs and calculating health costs (medical expenses). The results of the study indicate that the entry of oil palm companies brought socio-economic changes to the hamlets that were close to the company and far from the company. The hamlets close to the company changed after the entry of oil palm companies, this change was seen in land ownership and income, where before expansion the land was 48.96 Ha after expansion of 37.96 Ha with changes in income of Rp.1,202,932,000/year decreasing to Rp.1,176,332,000/year on.Hamlets that are far from the company do not experience changes in land area but experience an increase in income, this is because their land is not polluted due to palm oil waste so that the plants they plant do not die, before and after the land area remains the same 56.91 Ha.Previous income was Rp. 1,232,218,000/ year after increasing to Rp. 1,308,694,000/year.In the social conditions the impact caused by the entry of oil palm companies is health where the costs of the community spent this year Rp.3,647,500/year with a history of diseases such as fever, cough, skin disease suspected of the impact of factory waste.Keyword: Economy, Income, Land Function, Oil Palm, Social.